(3eONd Edi JGQjN fTQ GdJQGK GdYQHj ;s (3eY eMGVQI Yf GdJUMja hGdJMQja (B/s - (3GdWfGMj, eMehO eMeOs 1935-1999 ((3GdbGgQI(B- (3eUQ(B:s (3ecJHI GdNGfLi ,s, 1984)
(3jJfGhd cJGH (B((3eONd Edi JGQjN fTQ GdJQGK GdYQHj(B) (3GdPj bGe HJCdjag eMehO eMeO GdWfGMj aj MhGdj (B(406) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdJQGK GdYQHj(B) (3eJVefG GdeMJhjGJ GdJGdjI (B: (3YTQI CSHGH ddJUMja ef hGbY JLQHJj GdTNUjI GdSHH GdChd (B: (3JTGHg QSe GdMQha hJSGhjgG YOOG eY EgeGd GdfbW, GdKGfj (B: (3GNJdGa GdNW GdYQHj Hjf eTQbj heZQHj, GdKGdK (B: (3YOe GdeYQaI HdZGJ GdbHGFd, GdQGHY (B: (3bQH GdMQha hHYOgG aj GdcdeI GdhGMOI Ch GdcdeJjf, GdNGeS (B: (3NOGY GdSeY hgh GdJUMja GdSeYj, GdSGOS (B: (3NaGA eYfi GdcdeI YfO GdfGSN Ch GdbGQF ajYOd HgG Edi cdeI eCfhSI, GdSGHY (B: (3GdLgd HZQjH cdGe GdYQH, hjJUd Hg GdLgd HCfeGW GdJYHjQ YfO GdbOeGA hGdLgd HSjGb GdcdGe, GdKGef (B: (3GdLgd HeUWdMGJ GdYdhe, GdJGSY (B: (3GdLgd HCSeGA GdHdOGf, GdYGTQ (B: (3GdEda hgh HGH ddJUMja hGSY YdGL XGgQI GdJUMja(B.s
(3HHdjhLQGajI (B: (3UaMI (B396-406.s
Keywords: (3fTQ s -- (3fTQ GdcJH GdJQGKjIs -- (3JGQjNs -- (3GdHdGO GdYQHjIs